Designing the flow-through parts of distribution systems for the PRG series planetary hydraulic motors - Panchenko, Anatolii; Voloshina, Angela; Boltyansky, Oleg; Milaeva, Irina; Grechka, Iryna; Khovanskyy, Sergey; Svynarenko, Maksym; Glibko, Olena; Maksimova, Maria; Paranyak Nаdiya (Eastern-European Journal of Enterprise Technologies, 2018)
Improved efficiency of using the self-propelled machines is defined by the existence of hydraulic machines for the actuators of active working elements and running systems. Hydraulic drives of self-propelled machines exploit planetary hydraulic motors. The advantage of these hydraulic motors is a possibility to install them directly to the actuators of drilling machines, conveyors, winches, motor-wheels, etc. The basic node, limiting the work of a planetary hydraulic motor, is the distribution system. A distribution system creates a rotating hydraulic field that enables the working cycle of a planetary hydraulic motor. Therefore, improvement of the structural parameters of the distribution system is an important field of research aimed at improving the output characteristics of the planetary hydraulic motor. We have developed a design diagram and proposed a mathematical apparatus which make it possible to explore the influence of structural parameters of the distribution system on the output characteristics of the planetary hydraulic motor. The study we conducted has established that the synchronicity of a hydraulic field rotation depends on the number of working chambers and is characterized by a kinematic diagram of the distribution system. Dependence of change in the total area of the flow section in the distribution systems for different kinematic circuits is cyclical in character with a fluctuation amplitude dependent on the kinematic diagram. We have substantiated rational kinematic diagram of the distribution systems. We identified a zone where hydraulic losses are formed. The losses are caused by local resistances, when the working fluid passes along the distributing windows of the sleeve valve and the distributor. We have developed an algorithm for designing the flow-through parts. It enables the application of rational kinematic diagrams of the distribution system in order to improve the output characteristics of the planetary hydraulic motor.